Youth Social Exclusion in Australian Communities: A New Index - Abello, A.; Cassells, Rebecca; Daly, A.; D'Souza, G.; McNamara, R. (Springer Netherlands, 2015)
Social exclusion is a multi-dimensional measure of disadvantage that spans a number of aspects of an individual's life that impact upon their current and future wellbeing. For young people at an important life stage transitioning from childhood to adulthood, contributing factors to social exclusion and the consequences of social exclusion will vary. Using specialised data from the 2011 Australian Census, supplemented with national school assessment data, we use a domains approach to construct an index that is representative of youth at risk of social exclusion, using a combination of principal components and equal weighting techniques. The index provides important information that can inform direct policy action, especially in areas where the extent of relative multi-dimensional disadvantage is worse